AM-CSD Standards Metrics Support Project Management To Enhance Assessment of CSS Development - Abdulaziz Ahmed Thawaba,; Azizul Azhar Ramli,; Mohd. Farhan Md. Fudzee, (Applied Information Technology And Computer Science, 2022)
Critical Systems (CSS) are found in our everyday surroundings, such as medical, transportation, and aerospace systems. CSS failures may be a direct cause of harm to human life or environmental destruction. According to some studies, 60% of CSS failures can be reduced by optimizing the development processes. Therefore, CSS developers face difficulties in choosing appropriate metrics that help find errors, enhance implementation processes, and ensure compliance with standards. There are many metrics for project management (MPM) that improve project evaluation, but there is still a gap to reduce errors and ensure a reliable product. The Assessment Metrics for Critical System Development (AM-CSD) is an MPM tool. AM-CSD metrics improve CSS development by evaluating development processes from the initial stage to the closure stage. This paper discusses AM-CSD metrics using a case for train system project development.